Association of the use of manual thrombus aspiration with intracoronary thrombotic burden in patients with ST segment elevation myocardial infarction in the real world (2020)
Introduction: Although the routine use of manual thrombus aspiration (MTA) in patients with ST-elevation myocardial infarction (STEMI) provides no benefit compared to conventional primary percutaneous coronary intervention (PCI), the use of this technique in the real world could be associated with the intracoronary thrombotic burden. The objective of this study is to evaluate whether the use of MTA is directly related to a high intracoronary thrombotic burden as defined by the Thrombolysis in Myocardial Infarction (TIMI) scale, in patients with STEMI.Methods: Descriptive retrospective study of patients with a diagnosis of STEMI, in whom the use of MTA was assessed according to the coronary thrombus grading.Results: A total of 173 patients were included, with a mean age of 62 years, of whom 78% were male. Manual thrombus aspiration was performed in 52 (30%) of these patients, 98% (51/52) had a high thrombus burden (TIMI thrombus burden grade > 4), compared to 39.6% (48/121) of the patients who did not undergo MTA. Thus, a high thrombus burden was significantly related to the use of MTA (p<0.0001). There were no ischemic stroke or deaths due to cardiovascular causes in the MTA group during hospitalization.Conclusion: A high thrombus burden, as classified by the TIMI scale, was significantly associated with the use of MTA. This technique was not related with any major cardiovascular events. (C) 2019 The Authors. Published by Elsevier B.V.